Some nonfermented ethnic foods of Sikkim in India - Jyoti Prakash Tamang; Namrata Thapa (Journal of Ethnic Foods, 2014)
Sikkim, the Himalayan state of India has several ethnic foods which have not been documented. A field survey was conducted in randomly selected 370 households in Sikkim representing the major ethnic communities, namely, Nepali, Bhutia, and Lepcha. Information was collected on different types of nonfermented ethnic foods, as prepared and consumed by these inhabitants, the traditional method of preparation, mode of consumption, as well as culinary, socioeconomic, and ethnic values. We have listed more than 83 common and uncommon nonfermented ethnic foods of Sikkim consumed by different ethnic groups in Sikkim, India. Some of these foods have been documented and include achar, alum, chatamari, chhwelaa, dheroh, falki, foldong, kodoko roti, kwanti, momo, pakku, phaparko roti, phulaurah, ponguzom, suzom, thukpa or gya-thuk, and wachipa. Nutritional analysis, process technology development and packaging of these ethnic foods may boost ethnic food tourism in the region, which could in turn enhance the regional economy.